Comparative demography of two co-occurring Linum species with different distribution patterns - Münzbergová, Z (Plant biology (Stuttgart, Germany), 2013)
Understanding similarities and differences in population dynamics of closely related species is a key prerequisite in attempts to apply knowledge obtained in one species to another species, e.g., for the purpose of predicting future fate of populations of various rare species. It can be expected that species will have similar population dynamics if they are closely related and share similar habitats. Contrasting population sizes and distribution patterns may, however, indicate that the population dynamics will be different. To understand similarities and differences in population dynamics of closely related species, I studied demography of two congeneric endangered species, Linum flavum and L. tenuifolium co-occurring in dry grasslands. Linum flavum occurs with a lower number of large populations, while L. tenuifolium occurs as a large number of small populations. The results showed that L. flavum had higher population growth rates, relied more on survival and growth and its populations were more persistent. In contrast, populations of L. tenuifolium were more prone to extinction and frequent recolonisation was necessary for their survival in the landscape. This was in accordance with observed population sizes of the two species and their frequency in the landscape. The results indicate that despite being closely related and occurring in the same habitat types, the two Linum species have different growth strategies. The strong differences in population dynamics between the two species suggest that similarity in population sizes and frequency of the species in the landscape may be more important when attempting to transfer knowledge between species than is taxonomic relatedness.
Keywords: Flowers; druhová specificita; population size; rozmnožování; klíčení; demografie; Seeds; stadia vývoje; semena rostlinná; Flax; sexual reproduction; Species Specificity; ekosystém; flax; Czech Republic; Česká republika; Biomass; habitat occupancy; Life Cycle Stages; Reproduction; terminal velocity; Closely related species; květy; biomasa; len; Ecosystem; life-table response; Demography; seed mass; Germination